Implementasi Pengelompokan Kelas Berdasarkan Kemampuan Akademik di MI Mambaul Ma’arif Denanyar Jombang - Sholihah, Umi Hanifatus; Dyah, Eko Wahyu; Fitriyah, Nurul; Saleh, Chaerati (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
Class grouping in educational institutions, especially in elementary schools, has been discussed for a long time, but is still relevant to the current educational context. Class grouping strategies have been studied by several educational researchers because of their considerable benefits for teachers and students. This study aims to determine the implementation of class grouping at MI Mambaul Ma'arif Denanyar Jombang, the purpose of class grouping, and the impact that arises from class grouping. This type of research is a quantitative descriptive research with data collection techniques through observation, interviews, and documentation. The results obtained in this study are the implementation of class grouping at MI Mambaul Ma'arif Denanyar Jombang based on students' academic abilities. In determining the grouping of madrasa students using measuring tools in the form of tests and a ranking system. The purpose of class grouping at MI Mambaul Ma'arif is to facilitate teachers in planning, implementing and assessing learning. In its application, it also has a positive impact, including optimizing student understanding and making it easier for teachers to deliver material. And the negative impact is, a negative view of classes that have low academic abilities. Therefore, to minimize this negative impact, madrasas apply the naming of each class using the names of dzuriyah pondok and the names of wali songo.